Audit Siklus Kas: Peran dalam Mitigasi Fraud dan Tata Kelola Keuangan yang Akuntabel - Fajri Auliah Salsabila; Lisa Susilah Roi Ratnam; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the urgency of cash cycle audits in fraud prevention and accountability improvement through a Systematic Literature Review (SLR) approach. Cash, as the most liquid asset, has the highest vulnerability to fraud, making the implementation of audits in this cycle a fundamental element in strengthening financial governance. This study collects and reviews literature from national and international journals discussing internal auditing, cash control, fraud prevention, and accountability. Selection is based on relevance, methodological suitability, and source credibility, then analyzed using content analysis techniques. The results of the study show that cash cycle audits play a significant role in detecting discrepancies, assessing the effectiveness of internal controls, and ensuring compliance with operational procedures and regulations. In addition, the competence of internal auditors, the use of information technology, and the integration of internal control systems have been proven to strengthen fraud detection and prevention capabilities. These findings confirm that cash cycle audits not only serve as a verification tool, but also as a strategic mechanism to improve the transparency, accountability, and reliability of an organization's financial management.